What transformation can you apply to y=sqrtx to obtain the graph y=-sqrt(1/6(x-11)?

1 Answer
May 20, 2017

See below.

Explanation:

The second graph is basically just a modification of y = sqrt(x).

First, sqrt(x-11) is multiplied by a coefficient of -sqrt(1/6). Essentially, this means that the y-value of the second equation is -(1/6) times the y-value of y=sqrt(x).

Finally, because 11 is subtracted from x within the square root, the graph shifts 11 units to the right.

I have attached the graphs of both equations for reference.
enter image source here